AS ABORDAGENS DO TEMA MEIO AMBIENTE PELOS LIVROS DIDÁTICOS E PROFESSORES DA QUINTA SÉRIE DO ENSINO FUNDAMENTAL - Voichicoski, Marcia Silvana Rodrigues (2011)
The main discussion in this work is about the approaches of the environment theme adopted by school books and teachers in the fifth grade. The objective of this study was to analyze the approaches to the theme as well as the teachers‟ practice in a fifth grade class in a municipal public school in Palmeira, Paraná. The ideas of Leff (2001), Carvalho (2004, 2006), Reigota (1995, 2009), and Sauvé (2005) composed the theoretical framework. The methodology used was case study with qualitative approach. Data collection was carried out through interviews with the teachers, lesson observation, lesson plan analysis and document research with the school books. The content analysis proposed by Bardin (1977) was employed to data analysis. Results revealed: 1) The main approaches of the theme „environment‟ in school books were: resourcing, anthropocentric, problematic and naturalistic, among the teachers it was: problematic, physical space, anthropocentric and resourcing; 2) schoolbooks are used as support by all the teachers mainly to assign exercises, which are selected by them according to how easy or difficult they are (the easier ones are chosen); 3) Teachers acknowledge that the schoolbook has limitation, however, if used at the teachers‟ discretion might promote environmental awareness. Considering the results, several approaches are available which can be related to the theme „environment‟, however, lesson observation revealed that few approaches are used, namely, the resourcing, problematic and anthropocentric.